2021
DOI: 10.3390/curroncol28050305
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomic Analysis of Colon Cancer Tissue Revealed the Reason for the Worse Prognosis of Right-Sided Colon Cancer and Mucinous Colon Cancer at the Protein Level

Abstract: To clarify the molecular mechanisms underlying the poor prognosis of right-sided and mucinous colon cancer at the proteomic level. A tandem mass tag-proteomics approach was used to identify differentially expressed proteins (DEPs) in colon carcinoma tissues from different locations and with different histological types to reveal the underlying mechanisms of these differences at the protein level. In additional, the DEPs were analyzed using bioinformatics methods. The proteomics profiles among colon cancers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…STRING analysis further indicated candidate genes were clustered into three pathways: tRNA aminoacylation for protein translation and mitochondrial translation, mRNA splicing and translation ( Figure 1 E). Several RBP candidates which have been identified as oncogenes in CRC were identified and ranked high in our screening, including EIF6, 16 FARSA, 17 RRP12 18 and EFL1 19 ( Figure 1 E). Then, we explored The Cancer Genome Atlas (TCGA) database and analyzed by The University of ALabama at Birmingham CANcer data analysis Portal (UALCAN) data analysis portal and found that 85% of RBP candidates are highly expressed in CRC tumors ( Figure S1 C).…”
Section: Resultsmentioning
confidence: 97%
“…STRING analysis further indicated candidate genes were clustered into three pathways: tRNA aminoacylation for protein translation and mitochondrial translation, mRNA splicing and translation ( Figure 1 E). Several RBP candidates which have been identified as oncogenes in CRC were identified and ranked high in our screening, including EIF6, 16 FARSA, 17 RRP12 18 and EFL1 19 ( Figure 1 E). Then, we explored The Cancer Genome Atlas (TCGA) database and analyzed by The University of ALabama at Birmingham CANcer data analysis Portal (UALCAN) data analysis portal and found that 85% of RBP candidates are highly expressed in CRC tumors ( Figure S1 C).…”
Section: Resultsmentioning
confidence: 97%
“…This downregulation of the ACE2/Ang-(1-7)/Mas signaling axis may contribute to tumor progression and metastasis. 44 This regulatory axis provides a partial explanation for the low expression of ACE2 in colonic mucinous adenocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…These previous studies included not so many patients. Additionally, it has been reported that right-sided colon cancer was signi cant different from left-sided colon and rectal cancer in terms of long-term prognosis and cancer biology [13][14][15]. However, as far as we know, studies investigating the prognostic signi cance of sarcopenia among patients with left-sided colon or rectal cancer remain scarce.…”
Section: Introductionmentioning
confidence: 99%